The Relationship of Age with TNF-α Levels in Pregnancy and Abortion - Monika, Cici; Revilla, Gusti; Karmia, Hudila Rifa; Nurhajjah, Siti; Welan, Rahmani (Fakultas Kedokteran Universitas Andalas, 2026)
Introduction: Tumor Necrosis Factor Alpha (TNF-α) plays a crucial role in the early control of abortion. This increase can be influenced by age. The purpose of this study was to analyze the relationship between age and TNF-α in both normal pregnancies and abortion. Method: The type of research is analytic with a cross sectional design, collecting samples using total sampling technique, resulting in 36 patients who were subsequently assessed for TNF-α levels at the Biomedical Laboratory of Andalas University. The source of research data is secondary data. Data analysis involved the Spearman correlation test, Independent T-test, and Mann-Whitney test. Result: The average gestational age was younger, the average maternal age was older, and the average TNF-α levels were higher in abortion compared to normal pregnancy. The BMI of all patients was normal. There is a significant difference between age in normal pregnancy and abortion (p = 0.001), there is no relationship between age and TNF-α levels in normal pregnancy (p = 0.429), there is no relationship between age and TNF-α levels in abortion (p = 0.862), and there is no difference in TNF-α levels between normal pregnancy and abortion (p = 0.248). Conclusion: there is a significant difference between age in normal pregnancy and abortion.